SPECIFIC LEGAL SITUATION IN THE COLLECTOR ACTIVITY IN RUSSIA - Yuriy V. Belyanov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article investigates the specific legal situation in the activity of collector agencies dealing with recovery of debts of individuals and organizations in the Russian Federation and legal norms that must guide collectors in their work. The notion of collector activity was defined and stages of debt recovery were classified. World practices of such organizations were reviewed and specific legal regulation used in foreign countries was shown. The author explains the necessity to adopt a separate legal act regulating the order of debt recovery by collector agencies and discloses specific interaction of debtors and collector agencies which could prevent the infringement of parties' interests.